Recent drug development of dorzagliatin, a new glucokinase activator, with the potential to treat Type 2 diabetes: A review study - Yu Jiang; Luyao Wang; Zhenhua Dong; Baotian Xia; Shuguang Pang (Journal of Diabetes, 2024)
Abstract Type 2 diabetes mellitus (T2DM) is a complicated disease related to metabolism that results from resistance to insulin and sustained hyperglycemia. Traditional antidiabetic drugs cannot meet the demand of different diabetes patients for reaching the glycemic targets; thus, the identification of new antidiabetic drugs is urgently needed for the treatment of T2DM to enhance glycemic control and the prognosis of patients suffering from T2DM. Recently, glucokinase (GK) has attracted much attention and is considered to be an effective antidiabetic agent. Glucokinase activators (GKA) represented by dorzagliatin could activate GK and mimic its function that triggers a counter‐regulatory response to blood glucose changes. Dorzagliatin has shown great potential for glycemic control in diabetic patients in a randomized, double‐blind, placebo‐controlled Phase 3 trial (SEED study) and had a favorable safety profile and was well tolerated (DAWN study). In the SEED study, dorzagliatin significantly reduced glycosylated hemoglobin (HbA1c) by 1.07% and postprandial blood glucose by 2.83 mol/L, showing the great potential of this drug to control blood glucose in diabetic patients, with good safety and good tolerance. An extension of the SEED study, the DREAM study, confirmed that dorzagliatin monotherapy significantly improved 24‐h glucose variability and increased time in range (TIR) to 83.7% over 46 weeks. Finally, the clinical study of dorzagliatin combined with metformin (DAWN study) confirmed that dorzagliatin could significantly reduce HbA1c by 1.02% and postprandial blood glucose by 5.45 mol/L. The current review summarizes the development of GK and GKA, as well as the prospects, trends, applications, and shortcomings of these treatments, especially future directions of clinical studies of dorzagliatin.